HUBUNGAN TINGKAT PENDAPATAN DENGAN TINGKAT KONSUMSI MASYARAKAT DI KECAMATAN BONTONOMPO KABUPATEN GOWA - Ikram, Muhammad; AM, Sanusi (Jurnal Ekonomi Balance, 2014)
This study uses time series data obtained from the Central Bureau of Statistics (BPS) in 2015 research method used is to use the formula Correlation data processing that is using Peason Correlation Analysis to know the relationship between variables with the help of SPSS For Windows Release 16. That income and level of public consumption there is a significant relationship to the level of income with the average consumption level of each kecacam. This research expects the sub-district government to create more and more job opportunities in order for the people of each bias to have a decent income and meet their consumption needs.